STRATEGI PENGEMBANGAN KOMPETENSI GURU DALAM MENGHADAPI TRANSFORMASI DIGITAL UNTUK MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA PENDIDIKAN - Virda Andhara Sofia; Joko Sutarto; Barokah Isdaryanti (STKIP Subang, 2026)
Digital transformation has significantly changed the educational landscape and requires teachers to possess competencies that align with technological advancements. From the perspective of educational human resource management, teacher competency development is considered a strategic effort to enhance teacher quality and improve overall educational performance. This article aims to analyze strategies for developing teacher competencies in response to digital transformation and their implications for improving the quality of educational human resources. This study employed a qualitative approach using a literature review method. The data were collected from scientific journal articles, books, international organizational reports, and educational policy documents, focusing on publications from 2023–2025. The collected data were analyzed using content analysis through the processes of identification, classification, interpretation, and synthesis of relevant research findings. The results indicate that teacher competency development should be implemented continuously through needs-based training, continuous professional development, professional learning communities, coaching, mentoring, and strong instructional leadership from school principals. However, its implementation still faces several challenges, including unequal digital infrastructure, varying levels of teachers’ digital literacy, and unequal access to professional development programs. Therefore, integrated and sustainable educational human resource management policies are essential to strengthen teacher competencies, improve the quality of educational human resources, and enhance learning quality in the era of digital transformation.